Recent Advances in Synthetic Strategies to 2,3-Dihydrobenzofurans - Laurita, Teresa; D’Orsi, Rosarita; Chiummiento, Lucia; Funicello, Maria; Lupattelli, Paolo (Synthesis, 2020)
This review gives an overview on recent developments in methods for the construction of compounds with the 2,3-dihydrobenzofuran core in the period 2012 to 2019. Interest in 2,3-dihydrobenzofurans is constantly increasing. The methods are divided into intermolecular and intramolecular approaches. Intermolecular approaches are subdivided according to the parent intermediate for the key reaction, while intermolecular approaches are subdivided according by which bond is formed in the key reaction. The transformation of benzofurans to dihydrobenzofurans and other miscellaneous methods are also discussed. Approaches useful for the synthesis of natural products are emphasized.1 Introduction2 Intermolecular Approaches2.1 o-Quinone Methides and o-Quinones2.2 p-Quinone Methides and p-Quinones2.3 Nitrogen-Containing Phenols and Quinones2.4 o-Hydroxyphenylcarbonyl Derivatives and Phenols2.5 Miscellaneous3 Intramolecular Approaches3.1 O–C2 Bond Forming3.2 C2–C3 Bond Forming3.3 C3–Aryl Bond Forming3.4 O–Aryl Bond Forming4 From BF to DHB5 Rearrangements and Aromatizations
Keywords: dihydrobenzofurans; cyclizations; natural products; carbenes; nucleophiles; stereoselective synthesis